Enzyme replacement therapy on hypophosphatasia mouse model. Issue 2 (27th August 2013) - Oikawa, Hirotaka; Tomatsu, Shunji; Haupt, Bisong; Montaño, Adriana M.; Shimada, Tsutomu; Sly, William S.
Abstract: Hypophosphatasia (HPP) is an inborn error of metabolism caused by deficiency of the tissue‐nonspecific alkaline phosphatase (TNSALP), resulting in a defect of bone mineralization. Natural substrates for this ectoenzyme accumulate extracellulary including inorganic pyrophosphate (PPi), an inhibitor of mineralization, and pyridoxal 5‐phosphate (PLP), a co‐factor form of vitamin B6. Enzyme replacement therapy (ERT) for HPP by functional TNSALP is one of the therapeutic options. The C‐terminal‐anchorless human recombinant TNSALP derived from Chinese hamster ovary cell lines was purified. TNSALP‐null mice ( Akp2 ‐/‐ ), an infantile model of HPP, were treated from birth using TNSALP and vitamin B6 diet. Long‐term efficacy studies of ERT consisted of every 3 days subcutaneous or intravenous injections till 28 days old (dose 20 U/g) and subsequently every 3 days intravenous injections for 6 months (dose 10 U/g). We assessed therapeutic effect by growth and survival rates, fertility, skeletal manifestations, and radiographic and pathological finding. Treated Akp2 ‐/‐ mice grew normally till 4 weeks and appeared well with a minimum skeletal abnormality as well as absence of epilepsy, compared with untreated mice which died by 3 weeks old. The prognosis of TNSALP‐treated Akp2 ‐/‐ mice was improved substantially: 1) prolonged life span over 6 months, 2) improvement of the growth, and 3) normal fertility. After 6 months of treatment, we found moderate hypomineralization with abnormal proliferative chondrocytes in growth plate and articular cartilage. In conclusion, ERT with human native TNSALP improves substantial clinical manifestations in Akp2 ‐/‐ mice, suggesting that ERT with anchorless TNSALP is also a potential therapy for HPP.